2017
DOI: 10.1530/joe-16-0583
|View full text |Cite
|
Sign up to set email alerts
|

Gja1 acts downstream of Acvr1 to regulate uterine decidualization via Hand2 in mice

Abstract: Although has been proved to play an important role in uterine decidualization, its regulatory mechanism remains largely unknown. Here, we showed that was highly expressed in the decidual cells and promoted the proliferation of uterine stromal cells and expression of and, which were two well-known differentiation markers for decidualization. Further analysis revealed that might act downstream of and cAMP to regulate the differentiation of uterine stromal cells. Administration of cAMP analog 8-Br-cAMP to siRNA-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Indeed, knockdown of Egr2 in Ewing sarcoma cell lines could decrease the proportion of cells in S phase (Grünewald et al., ). Simultaneously, Egr2 also stimulated the expression of Prl8a2 , Prl3c1 , and Pgr , the well‐established markers for uterine stromal differentiation during decidualization (Yu et al., ; Zhang et al., ). Taken together, these results indicate that Egr2 plays an important role during decidualization.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, knockdown of Egr2 in Ewing sarcoma cell lines could decrease the proportion of cells in S phase (Grünewald et al., ). Simultaneously, Egr2 also stimulated the expression of Prl8a2 , Prl3c1 , and Pgr , the well‐established markers for uterine stromal differentiation during decidualization (Yu et al., ; Zhang et al., ). Taken together, these results indicate that Egr2 plays an important role during decidualization.…”
Section: Discussionmentioning
confidence: 92%
“…To gain an insight into the role of Egr2 in stromal cell differentiation, we next tested its effects on the expression of prolactin family 8, subfamily a, member 2 ( Prl8a2 ), prolactin family 3, subfamily c, member 1 ( Prl3c1 ), and progesterone receptor ( Pgr ), which are well‐established markers for uterine stromal differentiation during decidualization (Yu et al., ; Zhang et al., ). The result suggested that uterine stromal cells transfected with Egr2 siRNA revealed a marked decline in the expression of Prl8a2 , Prl3c1 , and Pgr compared with cells transfected with control siRNA (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, knockdown of Hmgn5, which was a novel discovered member of Hmgn family and crucial for decidualization [15], enhanced the expression of Hmgn2 in uterine stromal cells (our unpublished data), suggesting that Hmgn2 may functionally compensate the role of Hmgn5 in stromal differentiation. Further analysis revealed that Hmgn2 could stimulate the expression of Hand2 whose knockdown damaged the stromal differentiation in both mice and human [30, 34], implying that Hand2 may be a downstream regulator of Hmgn2 during decidualization. Previous studies have established that Hmgn2 was involved in transcriptional regulation of numerous genes by affecting histone modifications and activity of ATP-dependent chromatin remodeling complexes, or binding to chromatin regulatory sites such as Dnase I-hypersensitive sites, enhancers and promoters [11, 14, 29, 35], but the regulatory mechanism of Hmgn2 on the expression of Hand2 in uterine stromal cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that uterine decidualization is accompanied by elevated intracellular cAMP levels which prominently activates protein kinase A (PKA) signal transduction pathway [18,19]. In uterine stromal cells, cAMP analogue 8-bromoadenosinecAMP (8-Br-cAMP, 500 μM) up-regulated the expression of Hmgb1 at 48 h, whereas PKA inhibitor H89 (10 μM) abrogated the up-regulation of Hmgb1 elicited by 8-Br-cAMP (Fig.…”
Section: Hmgb1 Mediates the Effects Of Camp On The Differentiation Ofmentioning
confidence: 99%